Hyperbolic cross and complexity of various classes of linear ill-posed problems - Myleiko, G. L.; Solodkii, S. G. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
The present paper is a survey of the latest results obtained in the fields of information and algorithmiс complexity ofseverely ill-posed problems.